2020
DOI: 10.1111/jrh.12444
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Miners During the Coronavirus Disease‐2019 (COVID‐19) Pandemic

Abstract: Miners constitute an underserved, isolated, medically vulnerable, and often underinsured, rural population. 1 In the southwestern United States (US), most miners are Hispanic or American Indian, and high school dropouts. 1 The recent re-emergence of pneumoconioses 2 has created a challenge for rural mining communities in the US. Rural residents also experience a higher prevalence of, and deaths from, chronic obstructive pulmonary disease (COPD) than nonrural residents. 3 Rural miners similarly are at greater r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
14
0
3
Order By: Relevance
“…In addition, these workers usually perform jobs in an enclosed space and have close contact with each other. Hence, they are susceptible to COVID-19, which can easily outbreak once the virus appears among the population ( Sood et al, 2020 ). For example, COVID-19 hit the first Quantum’s Cobre Panamá mine and killed workers ( Latin America Copper, 2020 ).…”
Section: Transmission In Religious Organisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these workers usually perform jobs in an enclosed space and have close contact with each other. Hence, they are susceptible to COVID-19, which can easily outbreak once the virus appears among the population ( Sood et al, 2020 ). For example, COVID-19 hit the first Quantum’s Cobre Panamá mine and killed workers ( Latin America Copper, 2020 ).…”
Section: Transmission In Religious Organisationsmentioning
confidence: 99%
“…It has been reported that miners accounted for almost 20% of COVID-19 cases in Poland, where more than 10 coal mines had to be closed to contain COVID-19 ( Barteczko, 2020 ). Sood et al have called for intensifying the implementation of prevention and control measures among those workers ( Sood et al, 2020 ), such as providing primary care, health education, separate or isolated living spaces, disinfecting high-touch common areas, providing hand-washing stations and hand sanitizer, and providing adequate PPEs.…”
Section: Transmission In Religious Organisationsmentioning
confidence: 99%
“…14 Without a primary care provider, they are more likely to fall victim to misinformation about COVID-19, unnecessarily use emergency rooms, or use them too late. 15 In New York City, African Americans without providers could not receive COVID-19-related help even from the City's 311 nonemergency line, which was overwhelmed during the outbreak. 16 African Americans, particularly in the rural southeast, 17 are often suspicious of the health system, with a legacy of abuses such as the 1932-1972 Tuskegee syphilis study in rural Alabama, in which exclusively African American participants were allowed to die untreated.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…The different pandemics that humanity has experienced, such as Severe Acute Respiratory In December 2019, in Wuhan, the capital of Hubei province in China, the world has witnessed a novel infectious disease causing severe acute respiratory syndrome [4][5][6][7]. This disease, named as coronavirus by WHO, has rapidly turned from a local outbreak in Wuhan into the biggest pandemic of the last century (in Europe especially in Italy, in Africa and America (especially in the United States and India) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%